Effectiveness of Using Folklore Text-Based Learning Media Literacy in Class X Students of MAN Tg. Pura - Ahmad Drani; Abdurahman Adisaputera; Elly Prihasti Wuriyani (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This developmental research aimed to analyze the Effectiveness of Using Folklore Text-Based Learning Media Literacy in Class X Students of MAN Tg. Pura. This research was conducted at MAN 2 Tg Pura in class X students. The implementation of this research is planned to be carried out in February 2019 to April 2019. The data in this study are the results of observations, interviews, material validation questionnaires and learning media design, perception questionnaire results. teachers of the learning media developed, as well as student learning outcomes, amounting to 35 people. The observation data in the form of the value of learning to write saga text totaling 35 students so far and the results of interviews in the form of the opinions of 2 Indonesian language teachers regarding learning to write folklore texts (saga) were obtained from Indonesian students and teachers. Data in the form of material validation and learning media design were obtained from the validator/team of experts, as well as data on learning outcomes from students before and after using the developed learning media.  The results of students' learning ability in writing literacy-based folklore texts after using the developed learning media were in the "very good" category with an average value of 81.14 and the average value before using literacy-based folklore text learning media of 66, 57 which is in the "good" category. This proves that student learning outcomes are higher after using literacy-based folklore text learning media with a significance difference of 14.57%.